Truth Commission Archives as ‘New Democratic Spaces’: Table 1. - Jones, Briony; Oliveira, Ingrid (Journal of Human Rights Practice, 2016)

Documentation, Human Rights and Transitional Justice - Baumgartner, Elisabeth; Hamber, Brandon; Jones, Briony; Kelly, Gráinne; Oliveira, Ingrid (Journal of Human Rights Practice, 2016)
The role of testimony and documentation is crucial to human rights work in transitional contexts. Such evidence is vital in societies seeking to deal with a pas